(untitled) (Advances in Applied Mathematics and Mechanics, 2022)
In this paper, the local domain-free discretization (DFD) method is extended to large eddy simulation (LES) of fluid-structure interaction and the vortex-induced vibration (VIV) of an elastically mounted rigid circular cylinder, which is held in the middle of a straight channel, is numerically investigated. The wall model based on the simplified turbulent boundary layer equations is employed to alleviate the requirement of mesh resolution in the near-wall region. The ability of the method for fluid-structure interaction is demonstrated by simulating flows over a circular cylinder undergoing VIV. The cylinder is neutrally buoyant with a reduced mass m^∗ =11 and has a low damping ratio ζ =0.001. The numerical experiment of the VIV of a cylinder in an unbounded flow shows that the present LES-DFD method is more accurate and reliable than the referenced RANS and DES methods. For the cylinder in the middle of a straight channel, the effect of the channel height (d^∗ = d/D) is investigated. The variations of the response amplitude, vortex-shedding pattern and the length of the induced separation zone in the channel boundary layers with the channel height are presented.